XVIII. yüzyıl bestekârı Vardakosta Ahmet Ağa'nın Türk musikısindeki yeri ve önemi - Şenoğlu, Sevtap (Sosyal Bilimler Enstitüsü, 1994)
Tarih boyunca birçok devreler geçirmiş olan Türk Musikîsi, bu devreler içinde en verimli dönemini XVIII. yüzyılda yaşamıştır. XVIII. yüzyıl Türk Musikîsi için her yönden yeniliklerle dolu bir gelişme ve ilerleme dönemidir. Bu tez, musikîmizde böylesine önemli bir yer kaplayan XVIII. yüzyılın, dikkate değer musikişinaslarından Vardakosta Ahmed Ağa'nın eserleri üzerinde yapılan edebi ve teknik çalışmayı kapsamaktadır. Bu çalışmada ilk önce bestekârın tanıtılması amacıyla hayatı, eserle ri, yaşadığı yüzyıl ve eserlerinde kullandığı form yapıları hakkında bilgiler verilmiştir. Daha sonra bestekârın günümüze gelen eserleri hem edebî hem de müzikal açıdan tek tek incelenip, ebebî yönden sözlü eserlerde güfteleri oluşturan şiirlerin yapısı, özellikleri, konula rı, vezinleri; müzikal yönden usûl, makam ve form yapıları gözden ge çirilmiştir. Bunun sonucunda bestekârın Türk Musikîsindeki makam, usûl ve form yapılarını kullanma şekline göre üslûbu ile Türk Musikîsi rndeki yeri ve önemi belirlenmeye çalışılmıştır.

There are a lot of cultural values such as fine arts, music, literature, architecture, writing etc. Which bring the communitiy's cultural values up today throughout the history. There is no doubt, music is the most efficient, most impressive one among these values, because the community itself decauts its hearings, thoughts, livings, traditions and likewise everything that a human being can ever think logically in their music. Likewise, Turkish Music which is one of the values that bring and give life to Turkish community's cultural life from the past years to present has established the ancient civilizations throughout the history. Turkish Music which has a great consequence in our cultural life-has spent a very of periods cronologically from the beginning to our time, met some effects during these periods and has shown a lot of development. These developments become like this: We don't have enough knowledge about Turkish Music before 13til century which is as old as ancient Turkish civilization. Our music hasbeen systematized during this period in Middle Asia by the effects of Islamic thought and hes come to top level by the effects of İslam Religion when the ancient Turks came through Anatalia. These religious effects in our music have lasted till 13 century and then westernization have lessend these effects. 14 century is on era of dissolution and assembling in Turkish histroy. During this period, Turkish Music has shown sone activity. Our Music has gained two genius who are both composers and musicologists like Safiyüddin Abdülmümin Urmevi and Hoca Abdülkaadir Meragî. While Abdülkadir Merâgi-one of these precious musicians- has taken our music into scientific, technic and classic moulds, Safiyüddin has systemized our music and formed the Turkish scales scientifically IV through Maths and Physics which is still used today. In 15t'1 century, we see Padişah Sultan composers in our music. A very of production- which has a capital value-abour Turkish Music knowledge and over a hundred makams (collection of small tunes) have been written by the order of Murad II. who is one of the composers of this period and all there have been performed bay his orders. By the second half of this century, the Middle Ages have been closed and the New Ages have begun. The Sultans of this period Fatih Sultan Mehmed and Bayezid II. have protected the science, art and music. Musicology movements have continued as much as the Murad II.1 s period. In 16 century Turkish Musicology has not made any attemps. Our Music has gained two big composers by tha end of this century. These composers are Şeyh Abdülali in oral productions and Gazi Giray Han II. In stringed instrumental productions. In this century, we see sone anomymous songs which are called "Rumeli Folk Songs" as the new productions in Turkish Music. 17T century is a century which the glory and the brilliance of the 16 century continued Turkish Music has shown a great development in this period and comporotion and performance have developed a lot. In the middle of this century. Santur i Ali Ufkî Bey, took over hundred oral and stringed instrumental productions into notes, using the classic notation style. By this way the number of productions that come from 17th century to ourtime have been increased to that of past centuries. One of the biggest composers of classical Turkish Music is Buhurizade Mustafa Itrî Efendi after Meragalı Abdülkadir who lived in this century. After this century, in 18 century the development in our music has become so great and important that this period is consumed as the Renaissance period of Turkish Music. The biggest composers that grew up in this period, while hanging up to the traditions of the classic school with all of its necessities, also added some new discoveries to their productions. "Classical Period" in our music has reached to its peak by the participation of the genius composer Itrî in the first decade of this century. Also the period which is known as the "Tulip Period" in our history which is the second period of Ahmet III.' s sovereignty also meets this period. In this period, art, culture and music was protected by both Sultan and rich, ingenious men who have delicate taste. Turkish art and Turkish public music are close to each other in this period like as they used toke in 17tn century. In the second half of this period, especially the last quarter, Turkish Music has followed the classical traditions in Selim III. 's style. In this period, Turkish Music has searched for new ways by new tunes and new compositions of the new composers. Meanwhile Selim III. has noticed that the science in music is getting lost and he has needed notes in our music. Two new notes in two different systems have been invented by two big musicians, Hamparsum and Şeyh Abdülbaki Nasxr. By the entrance of Western Classic Music to our music, classic values have weakened. The popular composer of this century like Şakir Ağa, Dede Efendi, Emin Ağa gave productions with the clear effect of this culture. In our religious music the tradition of forms with all have continued their magnificence, and the Mevlevi* rites are mostly composed in this century. Among the periods which our music has spent from 131-" century to IS1-*1 century. 18 century is the period that related the past and future nearably and therefore this is the century in which our music has reformed. In this century our music has both continued its traditions and have taken the reforms into account. Shortly, 18 century has becoma landmark in our music and also the synthesis of the old and the new has been made in this century. The development in the end of thes synthesis have determined the fate of today's music. Te overall productions, composers and singers of the 18^ century of which has a great importance in our music, have some top qualities. From this way of thouht, the life and productions of Vardakosta Ahmed Ağa have been inquired, scrutinized of whom has a great importance among 18*-" century composers and in the and his style, his place and importance in Turkish Music has exposed to view in this thesis. In the first section of this work there
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1994
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 1994
Keywords: Müzik; Bestekarlar; Türk müziği; Vardakosta Ahmed Ağa; Music; Composer; Turkish music; Vardakosta Ahmed Ağa